THE EFFECT OF GENDER, CORPORATE GOVERNANCE, AND LOANS ON FINANCIAL DISTRESS IN MANUFACTURING INDUSTRIES - Tantania, Deitra; Ellis, Ellis; Rinaningsih, Rinaningsih (Universitas Pamulang, 2023)
This study aims to examine the influence of female roles, governance, and loans on the possibility of financial distress in manufacturing companies in Indonesia. Financial distress is measured through the Altman Z-score. The variables of female roles are measured based on the representation of female boards in the company while the variables of governance consist of the concentration of share ownership, the independence of the Board of Commissioners, the size of the Board of Directors, and the remuneration of the board. The loan variable is based on the value of the company’s long-term and short-term interest-bearing loans. The research was conducted based on a sample of 140 companies with 560 observations from 2018 to 2021. This research method uses binary logistic regression. The results of the study show that female board and concentration of share ownership had a significant negative effect on financial distress while loans had a significant positive effect. On the other hand, the independence of the Board of Commissioners, the size of the Board of Directors, and the remuneration of the board have no significant effect on the possibility of financial distress occurring in the company.